ATTEMPTS AT RAISING AWARENESS OF LANGUAGE AND LEARNING THROUGH COLLABORATIVE WRITING IN COLLEGE - Concario, Marcelo [UNESP] (Univ Federal Santa Catarina, Programa Pos-graduacao & Letras-ingles, 2018)
This paper is the result of classroom research with Radio/TV Studies undergraduates over a period of 16 weeks (60 hours) to investigate: (1) group cooperation/collaboration in the writing of two texts requiring online interaction; (2) students' comments about the language/strategies they practiced and learned, and the impact on their awareness of language and learning. Assessment of collaboration was based on the work of five groups. Comments about language learning/motivation/challenges were also expressed in a final presentation/portfolio. Interpretive analysis by the teacher-researcher shows that labor sharing is preferred, that learning is perceived to be more systematic because of the records of comments/corrections, and that students prefer to work mostly in class, which can be frustrating for advocates of autonomy in advanced language learning.
Keywords: English for Specific Purposes; Content-based Instruction; Higher Education; Language Awareness; Writing